What Is an Extension Program? - Glenn D. Israel; Amy Harder; Cheri Winton Brodeur (EDIS)
This 3-page fact sheet provides a definition for the term program and discusses the primary components included in a program. Written by Glenn Israel, Amy Harder, and Cheri Winton Brodeur and published by the UF Department of Agricultural Education and Communication, May 2011.